2022
DOI: 10.1002/cnma.202200119
|View full text |Cite
|
Sign up to set email alerts
|

Host‐Guest Assemblies of Cyanostilbenes and Cucurbit[8]uril: Luminescence Modulation, Photoreactivity Control and Energy Transfer Studies

Abstract: A series of di-cationic cyanostilbene derivatives possessing peripheral alkyl chains of variable lengths underwent host-guest complexation with CB[8] in aqueous media to produce higher order nano-and micro-structures of various morphologies and exhibited multi-color luminescence. Their complexation behavior was modulated by varying the ionic strength of the medium. The photoreactivity of the cyanostilbene chromophores in the CB[8] assemblies was found to be dependent on the length of the alkyl segment. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 178 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In the case of Recently, the Banerjee group reported an interesting example of fluorescent supramolecular polymeric assemblies based on the CB [8] and dicationic cyanostilbene derivatives 1 a-f comprising alkyl chains of different lengths (Figure 3). [39] Upon complexation with CB [8], cyanostilbenes with shorter chains 1 a-c (n � 6) mostly formed rectangular microstructures and their original weak cyan fluorescence transformed into the bright greenish-cyan or green one. In the presence of CB [8], the derivatives with longer chains 1 d-f (n � 8), formed nanosized hexagonal assemblies and nanofibers.…”
Section: Cb[n]-based Fret Systems For Modulation Of Color and Intensi...mentioning
confidence: 99%
“…In the case of Recently, the Banerjee group reported an interesting example of fluorescent supramolecular polymeric assemblies based on the CB [8] and dicationic cyanostilbene derivatives 1 a-f comprising alkyl chains of different lengths (Figure 3). [39] Upon complexation with CB [8], cyanostilbenes with shorter chains 1 a-c (n � 6) mostly formed rectangular microstructures and their original weak cyan fluorescence transformed into the bright greenish-cyan or green one. In the presence of CB [8], the derivatives with longer chains 1 d-f (n � 8), formed nanosized hexagonal assemblies and nanofibers.…”
Section: Cb[n]-based Fret Systems For Modulation Of Color and Intensi...mentioning
confidence: 99%
“…1a,10 Supratim Banerjee et al presented a supramolecule assembly of CB [8] with a series of cyanostilbene derivatives to produce multicolor luminescence, and then applied the host-guest system to an artificial light capture system to achieve turquoise, green, yellow, and pink luminescence. 11 George et al utilized CB [7] to encapsulate cationic phthalimide derivatives and further assembled them with LAPONITE s through electrostatic interactions to achieve efficient room-temperature phosphorescence for the photo harvesting energy transfer platform of fluorescent dyes. 12 Liu et al reported a CB [7]-based supramolecular polymer that established cell-cell interactions through hostguest recognition.…”
mentioning
confidence: 99%